2008
DOI: 10.1016/j.ejmech.2007.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of imidazopyridine anticoccidial agents: Part II

Abstract: Coccidiosis is the major cause of morbidity and mortality in the poultry industry. Protozoan parasites of the genus Eimeria invade the intestinal lining of the avian host causing tissue pathology, poor weight gain, and in some cases mortality. Resistance to current anticoccidials has prompted the search for new therapeutic agents with potent in vitro and in vivo activity against Eimeria. Recently, we reported the synthesis and biological activity of potent imidazo[1,2-a]pyridine anticoccidial agents. Antiparas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Et-PKG is essential for survival and represents a desirable therapeutic target (Scribner et al, 2007). Highthroughput screening of known kinase inhibitors resulted in the discovery of imidazopyridine derivatives as PKG inhibitors and broad-spectrum anticoccidial agents (Scribner et al, 2008). The imidazopyridine analogs were tested for in vitro efficacy via the Ten_K (Tenella kinase) assay, which measures inhibition of Et-PKG enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Et-PKG is essential for survival and represents a desirable therapeutic target (Scribner et al, 2007). Highthroughput screening of known kinase inhibitors resulted in the discovery of imidazopyridine derivatives as PKG inhibitors and broad-spectrum anticoccidial agents (Scribner et al, 2008). The imidazopyridine analogs were tested for in vitro efficacy via the Ten_K (Tenella kinase) assay, which measures inhibition of Et-PKG enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…The studied compounds are 107 imidazopyridine derivatives, which were taken from the literature (Liang et al, 2007;Scribner et al, 2007Scribner et al, , 2008Biftu et al, 2006); their structures are shown in Table 1. These compounds were tested for in vitro efficacy using the Ten_K (Tenella kinase) assay.…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental values for the IC 50 of the imidazopyridine anticoccidial compounds are taken from the literature [15] and presented in Table 1. The data set is randomly separated into a training set of 26 compounds and a test set of 12 compounds.…”
Section: Data Preparationmentioning
confidence: 99%
“…Different compounds containing the moiety imidazo[1,2-a]pyridine have significant biological applications such as anti-mycobacterial [15e21], anticancer [22,23], antiviral [24e27], antimicrobial [28e30], anti-HIV [31], antiulcer [32,33], antihelminthic [34] and anticoccidial activity [35,36]. As a result of our interest in the synthesis of imidazopyridine-containing compounds and their antimicrobial activity [37], we initiated a program directed towards the synthesis of the new imidazopyridine amide derivatives.…”
Section: Introductionmentioning
confidence: 99%